A Regression Model for Estimation of the Seasonal Component in Unemployment and Other Volatile Time Series - Brittain, John A. (The Review of Economics and Statistics, 1962)
John A. Brittain, A Regression Model for Estimation of the Seasonal Component in Unemployment and Other Volatile Time Series, The Review of Economics and Statistics, Vol. 44, No. 1 (Feb., 1962), pp. 24-36